Hill Region Fifth Five Year Plan and Annual Plan, 1974-75 Government of Uttar Pradesh - Planning Commission (Planning Commission, 1974)
The hill region of the State comprises the eight districts of Dehra Dun, Naini Tal, Almoda, Pauri Garhwal, Tehri Garhwal, Pithoragarh, Chamoli and Uttarkashi, which lie in the North of the State along the Himalayas. The hill region is bounded by Tibet in North, Himanchal Pradesh in the West, Nepal in the East.
Hill Development Department, Government of Uttar Pradesh